Collagen peptides affect collagen synthesis and the expression of collagen, elastin, and versican genes in cultured human dermal fibroblasts - Dierckx, Stephan; Patrizi, Milagros; Merino, Marián; González, Sonia; Mullor, José L.; Nergiz-Unal, Reyhan (Frontiers in Medicine, 2024)
Background Collagen is one of the major proteins of the skin and it is particularly important for its strength and resilience. Skin aging is a natural process that is characterized by the decrease and fragmentation of collagen in the dermis. Oral supplementation with collagen peptides has been clinically shown to have a positive effect on the skin condition. However, the mechanisms of aging-related changes synthesized by cells exposed to collagen are currently not well understood. Therefore, in this in vitro study, the mechanisms associated with collagen, elastin, and versican in human dermal fibroblasts were investigated after exposure to collagen peptides. Methods The effects of different concentrations of collagen peptides on cell viability and metabolism were analyzed. For gene expression analysis, human dermal fibroblasts were treated with collagen peptides. This was then followed by RNA extraction and DNA synthesis. Gene expressions of collagen type 1 (COL1A1), elastin (ELN), and versican (VCAN) were quantified by quantitative reverse transcription polymerase chain reaction (RT-qPCR). In addition, collagen levels were analyzed by confocal scanning laser microscopy using immunostaining. Results Collagen peptides tested in the study increased the expression of the relevant COL1A1, ELN, and VCAN genes in human dermal fibroblasts (p < 0.005). Furthermore, confocal microscopy showed increased collagen expression in the dermal fibroblast culture after treatment with the collagen peptides (p < 0.005). Conclusion These data provide cell-based evidence for the beneficial effects of exposure to collagen peptides on the skin’s collagen content and on the molecules that provide firmness and elasticity. This may support the hypothesis that collagen peptides are important for maintaining extracellular matrix (ECM) structure and skin regeneration.